High‐performance antistatic ethylene–vinyl acetate copolymer/high‐density polyethylene composites with graphene nanoplatelets coated by polyaniline. Issue 37 (28th May 2017) - Wang, Quan; Meng, Qingguo; Wang, Tinglan; Guo, Weihong
ABSTRACT: Graphene nanoplatelets coated by polyaniline (GNP@PANI) and ethylene–vinyl acetate (EVA) copolymer–high‐density polyethylene (HDPE) were used for the first time to prepare high‐performance antistatic composites through an effective method that combined solution mixing and melt blending. GNP@PANI nanocomposites were fabricated by in situ polymerization to improve the dispersion of graphene nanoplatelets (GNPs) in the EVA–HDPE matrix and the compatibility between the GNPs and the EVA–HDPE matrix. The GNP@PANI nanocomposites and EVA were first prepared as a premix through solution mixing, and then, the premix and HDPE were prepared as highly antistatic composites through melt blending. The dispersion of the GNPs in the EVA–HDPE matrix and the compatibility between the GNPs and the EVA–HDPE matrix were confirmed by field emission scanning electron microscopy and transmission electron microscopy observations. The GNP@PANI–EVA–HDPE composites met the requirements for antistatic materials when the content of the GNP@PANI nanocomposites was 5 wt % with only about 1 wt % GNPs. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45303. Abstract :